METODE BERCERITA UNTUK PEMULIHAN TRAUMA ANAK PASCA BENCANA GEMPA BUMI CIANJUR - Fitria Budi Utami; Uswah Uswah; Faisal Kemal; Wahyu Fajar Nugraha (LPPM Universitas Bina Bangsa, 2022)
The purpose of this community service is to carry out the obligations of the Tri Dharma of Higher Education as well as a form of concern and humanitarian mission for victims of earthquakes and landslides, especially children. Children as victims of natural disasters have their own trauma and this requires special attention and assistance. Moreover, based on the results of interviews and initial observations at the disaster site, storytelling activities and story books for children are still needed. This service method is a mentoring method which consists of four stages, namely the stages of socialization, preparation, implementation and preparation of reports as a form of evaluation. The results obtained from this activity were that the children felt happy and the team of volunteers also felt helped by the activity ideas and story books given because they felt there was still a lack of education staff at the disaster site